Analisis Titer Antibodi Covid-19 pada Pasien yang Belum Divaksin dengan Pasien yang Telah Divaksinasi Menggunakan Vaksin Covid-19 - Mustika Sari H Hutabarat; Rahmi Widiyawati; Gabriayah Hamzah (Institut Nalanda, 2026)
vaccine is fragment smallest or part (antigen) of inactivated organisms or weakened with objective For stimulate the formation of special antibodies, so if Then somebody infected by microorganisms body will can quick recognize And give resistance to organism That so that can minimize possibility infected disease even No until fall Sick . The Covid-19 vaccine being developed For overcome disease which are caused by by SARS-CoV-2 ever became a worldwide pandemic world , and proven with its implementation prokes health accompanied with giving vaccine lower number death And the pain caused by SARS-CoV-2 virus infection . Nevertheless Still There is community that considers that the Covid-19 vaccine does not own impact in lower number transmission disease And own impact negative to body , so No do vaccine against Covid-19. Research method This is study observation analytic with design Cross sectional research , with amount subject research divided into 32 people into 2 groups that is the subject does it Covid-19 vaccination ( without mention brands vaccine ) with a subject that doesn't do vaccine However confirmed Once exposed to Covid-19. results study This shows the average antibody in the subject already do vaccine mean 98.05 U/mL with group a subject that doesn't vaccinated However confirmed Once exposed to Covid -19 mean of 75.12 U/mL with sig value (p) 0.001 (<0.005) at T-Independent Test . From the results study This concluded that there is difference in Antibody titers on group the subject does it Covid-19 vaccination with group a subject that doesn't do vaccination.